Ovary maturation stages and histological investigation of ovary of the zebrafish (Danio rerio) - (:unkn) unknown (INST TECNOLOGIA PARANA, 2008)
Microscopic ovary features of Zebrafish were analyzed. Samples were fixed in Bouin's solution, mounted in parafin and cut into 6-7 mu m-thick slices which were stained with Hematoxylin and Eosin (HE), methylene blue and using Periodic-acid Schiff method (PAS). The thin sections in ultramicrotome with the thickness of approximately 0,5-0,7 mu m were examined by using Jeol electron microscope following contrasting with Uranyl Acetate-Lead Citrate. The zebrafish was an extremely dynamic organ in which follicles underwent asynchronous development. The oocytes of Zebrafish ovary were observed in various phases. The oocyte development of zebrafish was divided into four stages (primary growth, cortical alveolus, vitellogenic and mature oocyte). Oocyte diameters were observed to vary between 0.,08 mm and 0.76 mm.
Keywords: zebrafish; gonad; oocyte; development; FOLLICLE ULTRASTRUCTURE; OOCYTES